Constraints faced by farmers in adopting improved vegetable production technologies - Singh, Neeraj; Roy, Shubhadeep; SM, Vanitha; Rai, AB; Singh, VK; Singh, B (Vegetable Science, 2017)
Vegetable production in India constitutes around 60 per cent of its total horticultural production. India is the second largest producer of vegetables in the world next to China having an area of 9.40 million hectares producing 162.90 million tons of vegetables during the year 2013- 14. Vegetables play an important role in building nutritional and livelihood security in rural and peri-urban households due to their shorter duration, high yield and high value, nutritional richness, early economic returns and ability to generate on-farm and off-farm employment. The major states growing vegetables are West Bengal, Uttar Pradesh, Bihar, Madhya Pradesh, Gujarat, Maharashtra, Odisha, Karnataka, Andhra Pradesh and Tamil Nadu accounting for around 77 per cent of the total national vegetable production. With current level of vegetable production in the country (162.2 million tons), population (1.27 billion) and considering 25% postharvest losses and 5% export and processing, per capita availability of vegetables in our country is 250 g as against 300 g recommended dietary allowance (RDA)